Compound actuation system design for an advanced space transportation reusable orbiter - Zare Shahneh, Amir (MedCrave Group, 2018)
The SL-12 is a reusable space orbiter which offers the capability to go beyond the notion of a second generation space shuttle, and is targeted to be in operation in the year 2020. SL-12 Orbiter utilizes gimballing of the main rocket engines for control during ascent and typical aerodynamic surfaces for control during re-entry, approach, and landing. Power by wire (PBW) Actuation system is used for SL-12 based on All Electric Aircraft (AEA) approach. Electro Hydrostatic Actuators have been used for Primary Flight Control surfaces (Elevon, Body Flap and Rudder) and Thrust Vector Control for Main Engine Module, Electro Mechanical actuators have been used for Thrust Vector Control of Orbital Maneuvering System and Payload bay door. Dual redundant electric power supply channels are used for redundancy. Actuation System Safety and Reliability analysis has been done to ensure compliance and specification requirements.